Domestic violence and companion animals in the context of LGBT people's relationships. (September 2019) - Taylor, Nik; Fraser, Heather; Riggs, Damien W
The link between domestic violence and animal abuse has now been well established, indicating that where there is one form of abuse, there is often the other. Research on this link, however, has almost exclusively focused on heterosexual cisgender people's relationships. Lacking, then, is an exploration of the possibly unique links between domestic violence and animal abuse in the context of lesbian, gay, bisexual and trans (LGBT) people's relationships. In this article we adopt a feminist intersectional approach informed by Critical Animal Studies to advocate for a non-pathologising approach to understanding LGBT people's relationships with regard to the link between domestic violence and animal abuse.